(untitled) (Global Journal of Management and Business Research, 2014)
The study aims to identify the relationship between accountant skills and how they practice their roles in the banking sector with human resource factors, and if demographic factors may affect such a relation. To achieve the goals of the study, data was collected from Jordanian banks through a questionnaire specially designed for that and handed out to a sample of accountants, 120 questionnaires were valid for analysis, about 87.5% of the distributed questionnaires. The results of the study showed that there was a relationship between accountant skills and how they practice their roles in the banking sector with human resource factors. Furthermore, results also revealed a positive relationship between gender, age, and education as demographic factors affecting the realization of how accountant skills and practice roles in the banking sector effect human resource factors.